Improving information security in e-banking by using biometric fingerprint : a case of major bank in Malaysia - Mahmoud Musleh, Mahmoud Mohammed; Ba, Ismail Idrissa; Nofal, Karama M.A.; Ibrahim, Jamaludin (IJCSIS, USA., 2012)
In this paper biometric fingerprint technology will define and discuss as new best approach identification and authentication customers for online internet banking, and how biometric fingerprint will improve the internet banking protect its assets. Background will be produced to present how authentication and identification have developed and improved through the applications successful that have implemented biometric technology to protect its asset; then a case of major bank in Malaysia will be taken as a case study. By answering the question, why does biometric fingerprint need to come forefront as a great method of authentication in online banking environment? The findings have found that there are reasons and factors for higher security as a near perfect and biometric fingerprint authentication will be indicated to be the solution to answer this call.